Genetics of cardiovascular disease - Talmud, Philippa (Henry Stewart Talks, 2008)
Conventional CVHD risk factors, Multifactorial nature of CVD, Gene-environment interaction and how to test for it, Candidate gene approach to CVD genetics vs. genome-wide scans, Examples of the candidate gene approach and gene-environment interaction, APOE and smoking interaction, LPL and smoking, Mechanisms for these effects, Novel genes identified by genome-wide scans for CHD and lipid traits